Nuclear physics:an introduction - Patel, S. B. (New Age Internationa;l, 2018)
The book bridges the gap between a course on modern physics and an advanced formal treatise on nuclear physics. The treatment of topics is less formal, simple and direct. Physical ideas are given prominence and this has been done by informal discussions and many analogies ... It is a suitable text for any student who has been exposed to a college level course in modern physics and mathematical competence at the level of calculus and elementary vector analysis"-